Counselors In Addressing Gender Roles Community - Nuzliah Nuzliah; Juli Andriyani (Jurnal Counseling Care, 2020)
ABSTRACT Counseling is the process of providing assistance by professionals to individuals/groups of people to develop Effective Daily Livingg (EDL) and deal with Disrupted Effective Daily Livingg (D-EDL). The counselor's professionalism in dealing with various kinds of individual incidents/problems can be seen from the evaluation of the services performed and their implications in everyday life. In gender equality, professional counselors can distinguish how to provide solutions to gender (male and female). Gender differences must be understood by professional counselors. The research uses a qualitative research method with a literature review approach by finding, studying and analyzing theoretical references that are relevant to the problem. The research attempts to review a number of references in the form of books, scientific articles and other documents that discuss the concept of gender and gender characteristics, gender-based counseling and the role of counselors in gender. Kwyword : Counseling, gender, counselor, Male, Female ABSTRAKKonseling adalah proses pemberian bantuan yang dilakukan oleh tenaga professional kepada individu/ sekelompok orang untuk mengembangakan Kehidupan Efektif Sehari-hari (KES) dan  menangani Kehidupan Efektif Sehari-hari-Tergaggu (KES-T). Keprofesionalan konselor dalam menangani berbagai macam ragam kejadian/ permasalahan individu dampak dilihat dari evaluasi layanan yang dilakukan serta implikasinya dalam kehidupan sehari-hari. Dalam penyetaraan gender konselor yang profesional dapat membedakan cara memberikan solusi kepada gender (pria dan wanita). Perbedaan gender harus dipahami oleh konselor yang profesional. Penelitian menggunakan metode penelitian kualitatif pendekatan kajian literatur dengan mencari, mempelajari dan menganalaisis referensi teori yang relevan dengan permasalahan. Penelitian berupaya melakukan tinjauan terhadap sejumlah referensi berupa buku, artikel ilmiah dan dokumen lain yang membahas tentang konsep gender dan karakteristik gender, konseling berdasarkan gender serta peran konselor  dalam gender. Kata Kunci : Konseling, Jender, Konselor, Laki-laki, Perempuan